Analysis of ways to reduce energy resources consumption for building heating of telecommunication companies - Русу, Олександр Петрович; Rusu, Oleksandr P. (My University, 2019)
The increase of the traditional energy resources cost, due to the need to reduce carbon dioxide emissions, leads to an increase of the cost for services provided by telecommunications companies. One of the ways to reduce the use of traditional carbon energy resources is to replace them with alternative energy sources such as renewable chemical energy sources, solar and wind energy equipment, heat pumps and others. The most promising of these is the use of solar collectors. However, currently, most popular types and models of the solar collectors on the Ukrainian market are geared towards hot water supply systems, and their integration into existing air heating systems is related to the need to significantly modernize them. Thus, in practice, the modernization of existing air heating systems leads to many technical and organizational problems. At the same time, promising directions for utilization of solar radiation energy for the building heating are the use of air solar collectors and their integration with heat pumps. However, in Ukraine, this trend has not yet become widespread despite its undoubted advantages. The article discusses the methods of using solar collectors for the telecommunication companies’ building heating, which require minimal integration of them into already existing engineering systems of building. Two promising methods are considered: the use of solar air collectors and the integration of water solar collectors in existing air conditioning systems based on heat pumps. Attention is paid to the advantages of using air solar collectors to heat the premises. The proposed methods of using solar collectors can become the basis for the development of new facilities and systems for building heating, which will reduce the consumption of organic fuels and the environmental impact of the environment. Збільшення вартості традиційних енергоресурсів, що обумовлена необхідністю зменшення рівня викидів вуглекислого газу, призводить до збільшення вартості послуг, що надаються телекомунікаційними компаніями. Одним зі способів зменшення використання традиційних вуглецевих енергоресурсів є заміна їх альтернативними джерелами енергії, найбільш перспективним із яких є використання сонячних колекторів. Однак на сьогоднішній день більшість присутніх на українському ринку сонячних колекторів орієнтовані на системи гарячого водопостачання, а їх інтеграція в уже існуючі системи опалення пов’язана із необхідністю істотної модернізації останніх, що на практиці призводить до цілої низки технічних та організаційних проблем. У той самий час перспективними напрямками утилізації енергії сонячного випромінювання для обігріву приміщень є використання поки що не набув широкого розповсюдження, незважаючи на його безсумнівні переваги. У статті розглянуті методи використання сонячних колекторів для обігріву приміщень телекомунікаційних компаній, що потребують мінімальної інтеграції їх в уже існуючі інженерні системи будинків. Зокрема, розглянуто два перспективних методи: використання повітряних сонячних колекторів та інтеграція рідинних сонячних колекторів в уже існуючі системи кондиціонування на основі теплових насосів. Особливу увагу приділено перевагам використання повітряних сонячних колекторів для обігріву приміщень. Запропоновані способи використання сонячних колекторів можуть стати основою для розробки нових пристроїв та систем для обігріву приміщень, що дозволять зменшити витрати органічних видів палива та рівень екологічного навантаження на довколишнє середовище.
Rusu О. P. Analysis of ways to reduce energy resources consumption for building heating of telecommunication companies / О. P. Rusu // Наукові праці ОНАЗ ім. О. С. Попова. – 2019. – № 1. – С. 33-38.
Keywords: solar collector; air conditioning; heating system; heat pump; alternative / solar energy; сонячний колектор; кондиціонер; система обігріву; тепловий насос; альтернативна/сонячна енергетика; Research Subject Categories::TECHNOLOGY